1991
DOI: 10.1128/iai.59.11.4193-4200.1991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of granule proteins from human polymorphonuclear leukocytes which are bactericidal toward Pseudomonas aeruginosa

Abstract: Killing of Pseudomonas aeruginosa by a 55-kDa bactericidal protein (BP 55), a 30-kDa protein (BP 30), cathepsin G, elastase, and proteinase 3 has been compared. P. aeruginosa was resistant to killing by elastase and proteinase 3. BP 55 at a 50% lethal dose (LD50) of 0.23 ,ug of protein per 5 x 106 bacteria per ml killed P. aeruginosa and was far more active than BP 30 and cathepsin G. The LD5s of BP 30 and cathepsin G were 16.9 and 28.3 ,ug of protein per 5 x 106 bacteria per ml, respectively. Preincubation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…It has been proposed that this substitution may account for the resistance of this microorganism to cationic antibiotics, such as polymyxin B (12), and antibacterial proteins, such as BPI (also called CAP 57 [26,27] and BP 55 [9,31]).…”
mentioning
confidence: 99%
“…It has been proposed that this substitution may account for the resistance of this microorganism to cationic antibiotics, such as polymyxin B (12), and antibacterial proteins, such as BPI (also called CAP 57 [26,27] and BP 55 [9,31]).…”
mentioning
confidence: 99%
“…Farley et al found that 11 times the amount of CAP57 required to kill the rough LPS mutant was required to kill the smooth LPS strain of S. typhimurium (6). This difference in sensitivity to PMN bactericidal proteins was not due to a difference in the proteins, for BP55, B/PI, and CAP57 have the same N-terminal amino acid sequence and are very likely the same protein (24,27,35). Furthermore, although we have not carried out a comprehensive comparison, we have previously established that killing of a smooth strain of S. typhimurium required 300-fold more BP55 than did killing of a rough strain of E. coli or of the smooth strain P. aeruginosa type 1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…This 55,000-Da bactericidal protein (BP55) binds to the target bacteria and depolarizes the cytoplasmic membrane, which results in the cessation of amino acid transport and eventual cell death (16). Like the 57,000-Da cationic antimicrobial protein (CAP57) and the 59,000-Da bactericidal and permeabilityincreasing protein (B/PI), which bind to the lipopolysaccharides (LPS) from the outer membranes of Salmonella typhimurium and Escherichia coli (31, 37), respectively, BP55 binds to the LPS from P. aeruginosa (14,35).The outermost portion of the LPS, the O-polysaccharide side chain, plays an important role in the pathogenicity of most gram-negative bacteria, including P. aeruginosa (4, 23). O-polysaccharide side chains of smooth LPS can sterically hinder the formation of the complement membrane attack complex, thus conferring serum resistance to the bacteria (8, 17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LALF is a small basic protein that binds to and neutralises the effect of LPS in the coagulation cascade of the crab [12]. BPI binds to LPS and could participate in the homeostasis of LPSinduced response [13,14]. The structures of both, LALF and BPI, have been solved by X-ray crystallography 964 MORA, DE LA PAZ AND PÉREZ-PAYÁ and structural analysis has revealed putative LPSbinding sites located at solvent exposed amphipathic β-hairpin structures [12,15,16].…”
Section: Introductionmentioning
confidence: 99%